2010
DOI: 10.1007/s00464-010-1475-2
|View full text |Cite
|
Sign up to set email alerts
|

Gut oxygenation and oxidative damage during and after laparoscopic and open left-sided colon resection: a prospective, randomized, controlled clinical trial

Abstract: LPS seems to be associated with a better intra- and postoperative PtiO2. High-pressure PP may impair PtiO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
2
8
2
Order By: Relevance
“…Intestinal tissue oxygen pressure has been found to decrease significantly during mesentery traction in both laparoscopic and open colectomy. 19 The incidence of ischemia during laparoscopic procedures may be minimized by using the lowest acceptable intraabdominal pressure and by intermittent decompression and deflation during prolonged laparoscopic procedures, and by avoiding prolonged traction on the bowel during extracorporeal resection and anastomosis. Although more time is required for intracorporeal than for extracorporeal resection and anastomosis, the former may better maintain intestinal tissue oxygen pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal tissue oxygen pressure has been found to decrease significantly during mesentery traction in both laparoscopic and open colectomy. 19 The incidence of ischemia during laparoscopic procedures may be minimized by using the lowest acceptable intraabdominal pressure and by intermittent decompression and deflation during prolonged laparoscopic procedures, and by avoiding prolonged traction on the bowel during extracorporeal resection and anastomosis. Although more time is required for intracorporeal than for extracorporeal resection and anastomosis, the former may better maintain intestinal tissue oxygen pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The literature data about the effect of open and laparoscopic surgery techniques on parameters of oxidative stress are unequivocal. Gianotti et al [33] demonstrated that both laparoscopy and open colon surgery may cause oxidative damage during mesentery traction and immediately after the end of operation. Bukan et al [34] showed that both open and laparoscopic cholecystectomy techniques caused an increased oxidative stress; however, laparoscopy induces less significantly oxidative stress than open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26] Desuflation of the abdomen normalizes the IAP and splanchnic blood flow, and this may result in reperfusion resulting in a high generation of free radicals. The study 17 showed that oxygen tension compared with baseline values was only reduced when the IAP was 15 mm Hg (CO 2 ). However, these studies were primarily animal studies, case reports, or minor surgery with mostly indirect measuring techniques.…”
Section: Discussionmentioning
confidence: 98%
“…Power calculation was performed on the basis of baseline MDA from Gianotti et al 17 With a standard deviation of 0.3 mmol/L for MDA and a mean of 0.16 mmol/L with a risk of type I error of 5% and type II error of 20%, it was necessary to include 5 patients in each group. The data were tested for normal distribution with Kolmogorov-Smirnov test, and AA and DHA were normally distributed.…”
Section: Discussionmentioning
confidence: 99%